Harnessing the Values along the Food Supply Chain of Poultry Production in Nigeria - Fajemisin, A.N.; Ogunribido, T.Z. (Nigerian Journal of Animal Science, 2023)
This review assessed the numerous channels through which values can be harnessed along the supply chain in poultry farming in Nigeria with the attendant multiplicative effect on job creation in line with the sustainable development goal (SDG). The findings in this review highlight the present situation in the Nigerian poultry production system and possibility of enhancing per annum production. Literature is abundant with reports of many agricultural by-products that end up as wastes along the production system whereas these so-called wastes are a latent industry in disguise capable of generating wealth and bringing food to the table. This review also efficiently captured the concept of food security such that food can be made readily available to all people at all times and everywhere.